DLSU-D Green Innovations on Waste Management: Adoption of Greener Lifestyles in New Normal - J. Dinglasan, Joseph; P. Luyon, Jocelyn; E. Abiog II, Deodoro (Journal of Sustainability Perspectives, 2021)
De La Salle University-Dasmariῆas (DLSU-D) is one with the call to collective action in responding to global ecological crisis as it adapts to the new normal of creating a safe, sustainable, and healthy university where the experience of God is lived and shared. As the world is currently battling new challenges affecting the environment in the face of COVID-19 crisis, DLSU-D reiterates its stand to lead in sustainable practices that foster caring for our common environmental home. Under the Black Out! Green In! flagship program, which is the University’s green response to combat climate change, its Ecological Solid Waste Management Program (ESWMP) ventures into simple, low-cost, and low technology initiatives. Internal collaboration among faculty, students, and service providers as well as external partnerships with non-governmental organizations (NGOs) and local government units (LGUs) having similar environmental advocacies and lifestyle changing significantly contribute to the innovations and sustainability of the campus waste management program